Error Analysis in Using Passive Voice - Sukmawati Yasim; Hasnawiah Hasnawiah; Roni Roni (EDUVELOP, 2018)
This research scrutinizes find out To find out the student’s error in using passive voice at the Students of MA DDI Banua. The Objectives of the study are: (1) to obtain and identify the common error made by students in constructing Passive voice in Simple past tense and (2) to obtain the causes of errors in constructing Passive voice in simple past tense. The method used in this research was descriptive qualitative. In collecting data, the writer used 3 (three) types of techniques: Observation, interview and test. This research was carried out the students of MA DDI Banua. The population of the research are the students of MA DDI Banua in Academic year 2015/2016 with total number was 79 and Sample of the research will be taken by using random sampling technique. The researcher take language class since the researcher would like to know the students’ ability in language class about passive voice. The sample is from class XI with consist of 18 students. Based on the finding and discussion, the researcher concludes the highest until the lowest frequency and the percentage of errors made by students derives from Information of Passive Verb The writer gave a 20-item highest until the lowest frequency and the percentage of errors made by students derives from global error with 231 errors or 84.61%, local error with 42 errors or 15.39% and the highest until the lowest frequency and the percentage of errors in Information Error made by students derives from Verb 3 (196 errors or 40.55%), Object Pronoun (49 errors or 13.61%), Subject – Object (87 errors or 24.16%), Be (78 errors or 16.11).